Menelusuri Jejak Nabi: Kajian Living Hadis Dalam Mozaik Kehidupan Muslim Indonesia - Sumitra; Tajul Arifin (Yayasan Cendekia Gagayunan Indonesia, 2024)
This study is motivated by the fact that numerous phenomena of living hadith exist within the context of Indonesian society, focusing on religious practices based on the hadith of Prophet Muhammad (peace be upon him). The study identifies various forms of living hadith, such as traditions, written and oral forms, as well as practices, and analyzes their impact on the socio-religious fabric of the community. Using phenomenology and the sociology of knowledge, this research reveals the significant role of living hadith in enriching social and cultural religious practices while also highlighting its potential to cause social tensions. The findings indicate the need for a comprehensive and multidisciplinary approach to understanding the dynamics of Islam in Indonesia, as well as the importance of interdisciplinary dialogue in the development of living hadith using qualitative and ethnographic approaches.